'For me, it didn't seem as drastic a step as being controlled by insulin': A qualitative investigation of expectations and experiences of non‐insulin injectable therapy among adults with type 2 diabetes. Issue 2 (4th September 2021) - Holmes‐Truscott, Elizabeth; Schipp, Jasmine; Dunning, Trisha; Furler, John; Hagger, Virginia; Holloway, Edith E.; Manski‐Nankervis, Jo‐Anne; Shaw, Jonathan E.; Skinner, Timothy; Speight, Jane
Abstract: Aims: This qualitative study aims to explore beliefs, attitudes and experiences of injectable glucagon‐like‐peptide‐1 receptor agonists (GLP‐1RAs) use and discontinuation, as well as attitudes to further injectable treatment intensification, among adults with type 2 diabetes (T2D). Methods: Nineteen in‐depth semi‐structured interviews lasting (mean ± standard deviation) 45 ± 18 min were conducted, face‐to‐face ( n  = 14) or via telephone ( n  = 5). Transcripts were analysed using inductive template analyses. Eligible participants were English‐speaking adults with T2D who had recently initiated (≤3 years) GLP‐1RA treatment. Results: Participants were aged 28–72 years, who predominantly lived in metropolitan areas ( n  = 15), and had an experience of daily ( n  = 11) and/or once‐weekly ( n  = 13) GLP‐1RA formulations. Six participants had discontinued treatment and seven had trialled two or more formulations. Expectations and experiences of GLP‐1RA were related to the perceived: (1) symbolism and stigma of injectable diabetes treatment; (2) ease of injectable administration and device preferences; (3) treatment convenience and social impact; (4) treatment efficacy and benefits, and; (5) negative treatment side effects. Some participants reported increased receptiveness to insulin therapy following their GLP‐1RA experience, others emphasised unique concerns about insulin beyond injectable administration. Conclusions: This study provides a novel understanding of expectations and experience of non‐insulin injectables among Australian adults with T2D. Our data suggest expectations may be informed by attitudes to insulin therapy, while perceived treatment benefits (e.g. weight‐related benefits, administration frequency) may motivate uptake and ongoing use despite concerns. Experience of GLP‐1RA injections may impact receptiveness to future insulin use.